2015
DOI: 10.1214/15-aoas841
|View full text |Cite
|
Sign up to set email alerts
|

Quantile regression for mixed models with an application to examine blood pressure trends in China

Abstract: Cardiometabolic diseases have substantially increased in China in the past 20 years and blood pressure is a primary modifiable risk factor. Using data from the China Health and Nutrition Survey we examine blood pressure trends in China from 1991 to 2009, with a concentration on age cohorts and urbanicity. Very large values of blood pressure are of interest, so we model the conditional quantile functions of systolic and diastolic blood pressure. This allows the covariate effects in the middle of the distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Quantile regression model allows the predictor variable to have a more complex relationship with the response variable [26]. Our developed tree height’s conditional probability density functions for a given diameter (Eqs B.1, B.4, B.7, B.10 and B.13) enables us to write the quantile equation of the tree height to any desired conditional quantile of the height’s distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Quantile regression model allows the predictor variable to have a more complex relationship with the response variable [26]. Our developed tree height’s conditional probability density functions for a given diameter (Eqs B.1, B.4, B.7, B.10 and B.13) enables us to write the quantile equation of the tree height to any desired conditional quantile of the height’s distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Other methods or algorithms used to QR includes Barrodale-Roberts algorithm [82], Expectation-Maximization (EM) algorithm [83], Monte Carlo Expectation-Maximization (MCEM) algorithm [13,84,85], and Bayesian approach by Markov chain Monte Carlo (MCMC) procedure [86][87][88][89][90][91][92][93]. Longitudinal QR has been rapidly expanded in many areas, including investment and finance [94,95], economics [96], environmental science [97,98], geography [99], public health [100,101] and biomedical research [102][103][104][105]. In investment and finance areas, Bassett and Chen [94] utilized longitudinal QR to provide additional information from the time series data of portfolio returns based on the way style that affects returns at places other than the expected value of return.…”
Section: Qr Models For Longitudinal Datamentioning
confidence: 99%
“…It provided a full scan of information among time effects, education level, and years of experience in different wage quantile. In public health, Smith et al [100] revealed that the association between high blood pressure and living in an urban area has evolved from positive to negative, with the strongest changes occurring in the upper tail. In meteorology, Timofeev and Sterin [97] utilized longitudinal QR to analyze various changes in climate characteristics.…”
Section: Qr Models For Longitudinal Datamentioning
confidence: 99%
“…This is particularly the case owing to their contribution to the incidence of cardiovascular disease (CVD). A number of studies have found significant and linear relationships between SBP and DBP levels, and CVD morbidity and mortality 4 , 5 . Analysis of longitudinal data spanning 20 years confirms that SBP and DBP have continuous, graded, strong, independent, etiologically significant relationships to blood pressure-related risks, primarily incidence and mortality from coronary heart disease, stroke, and all CVDs 6 .…”
Section: Introductionmentioning
confidence: 99%